Similar incidence of coronavirus disease 2019 (COVID-19) in patients with rheumatic diseases with and without hydroxychloroquine therapy - Macías, Juan (PLoS One, 2021)
BACKGROUND: Hydroxychloroquine is not efficacious as post-exposure prophylaxis against coronavirus disease 2019 (COVID-19). It is not known whether as pre-exposure prophylaxis it may prevent COVID-19. OBJECTIVE: To compare the incidence of COVID-19 in Spanish patients with autoimmune rheumatic diseases treated with and without hydroxychloroquine. PATIENTS AND METHODS: Retrospective electronic record review, from February 27(th) to June 21(st), 2020, of patients with autoimmune inflammatory diseases followed at two academic tertiary care hospitals in Seville, Spain. The cumulative incidence of confirmed COVID-19, by PCR or serology, was compared between patients with and without hydroxychloroquine as part of their treatment of autoimmune inflammatory diseases. RESULTS: Among 722 included patients, 290 (40%) were receiving hydroxychloroquine. During the seventeen-week study period, 10 (3.4% [95% CI: 1.7%-6.7%] cases of COVID-19 were registered among patients with hydroxychloroquine and 13 (3.0% [1.6%-5.1%]) (p = 0.565) in those without hydroxychloroquine. COVID-19 was diagnosed by PCR in four (1.4%, 95% CI 0.38%-3.5%) subject with hydroxychloroquine and six (1.4%, 95% CI 0.5%-3.0%) without hydroxychloroquine (p = 0.697). Three patients on hydroxychloroquine and four patients without hydroxychloroquine were admitted to the hospital, none of them required to be transferred to the intensive care unit and no patient died during the episode. CONCLUSIONS: The incidence and severity of COVID-19 among patients with autoimmune rheumatic diseases with and without hydroxychloroquine was not significantly different.